The effectiveness of working memory training with individuals with intellectual disabilities – a meta-analytic review - Danielsson, Henrik; Zottarel, Valentina; Palmqvist, Lisa; Lanfranchi, Silvia (Frontiers in Psychology, 2015)
Working memory training has been increasingly popular in the last year. Previous studies has shown that children with intellectual disabilities have low working memory capacity and therefore have a great potential for improvement by this type of intervention. The aim of this study was to investigate the effect of working memory and cognitive training for children with intellectual disabilities. The effects reported in previous studies have varied and therefore meta-analysis of articles in the major databases was conducted. Inclusion criteria included to have a pretest-posttest design with a training group and a control group and to have measures of working memory or short-term memory. Ten studies with 28 comparisons were included. The results reveal a significant overall pretest-posttest small effect size for of working memory training for children with intellectual disabilities compared to controls. A mixed working memory approach, considering both verbal and visuo-spatial components and working mainly on strategies, was the only significantly effective training type with a medium effect size. The most commonly reported training type with 60 percent of the included comparisons, visuo-spatial working memory training, had a non-significant effect size that was close to zero. We conclude that even if there is an overall effect of working memory training, a mixed working memory approach appears to cause this effect. Given the few studies included and the different characteristics of the included studies, interpretations should be done with caution. However, different types of interventions appear to have different effects. Even if the results were promising, more studies are needed to better understand how to design an effective working memory intervention for this group and to understand if, and how, these short-term effects remains over time and transfer to everyday activities.